KIDDIESAFE APPLICATIONS: GAME-BASED LEARNING OF HEALTH EDUCATION AWARENESS AMONG PRIMARY SCHOOL STUDENTS (Journal of Creative Industry and Sustainable Culture, 2024)
In the digital age, modern educational institutions face the challenge of engaging a generation of students accustomed to interactive and visually stimulating content. This study explores how the KiddieSafe App, an educational tool infused with game design elements, helps students in primary schools learn issues of safety and cleanliness more effectively. Drawing from the concepts of Digital Game-Based Learning and the development of 21st-century skills, the app features bright animations, interactive quizzes, and an interactive interface to help engage young learners. A summative evaluation of Year 1 students in Sekolah Kebangsaan Jitra 3 shows that this app has the potential to enhance learning outcomes and increase students' engagement. Although there were minor usability issues, general feedback was positive, thus proving this application to have potential as an effective supplementary educational aid. Future enhancements will focus on content diversity and feedback mechanisms to make the learning experience as enriching as possible.